Case report: Venetoclax therapy in a boy with acute myeloid leukemia in Shwachman Diamond syndrome - Naviglio, Samuele; Grasso, Antonio Giacomo; Iacono, Chiara; Zanella, Giada; Kiren, Valentina; Giurici, Nagua; Verzegnassi, Federico; Maximova, Natalia; Rabusin, Marco (Frontiers in Pediatrics, 2023)
Shwachman-Diamond syndrome (SDS) is a rare bone marrow failure syndrome characterized by exocrine pancreatic insufficiency, bone abnormalities, progressive cytopenia, and predispositions to myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). AML is associated with a poor prognosis, and patients are also at an increased risk of organ toxicity and infectious complications from chemotherapy and hematopoietic stem cell transplantation (HSCT), thus leading to high rates of treatment-related morbidity and mortality. The BCL-2 inhibitor venetoclax has revolutionized the treatment of AML in elderly adults, especially for treatment-naive elderly patients who are ineligible for intensive chemotherapy. There is limited evidence on the use of venetoclax in pediatric patients with SDS-related MDS or AML. Here we report a case of a 16-year-old boy with SDS with a myelodysplastic syndrome that evolved into AML. The patient was treated with two cycles of conventional chemotherapy with fludarabine and cytarabine with an initial good response but immediate relapse and substantial toxicity. Treatment with venetoclax and azacytidine was started, with a substantial reduction of leukemic burden (good response on peripheral leukemic infiltration and partial response in the bone marrow after one course), yet it was followed by multiple infectious complications and worsening of general condition not allowing treatment to be continued, and the patient eventually died from multiorgan failure. With the limitations of observation of a single patient, our experience suggests that venetoclax/azacytidine combination therapy may represent a therapeutic possibility for patients with SDS and AML, even though it may be associated with significant toxicity.